The Ancient Writing Culture Of The Turanian Peoples (Eurasian Scientific Herald, 2025)
The article discusses the ancient writing culture of the peoples of Turan. It is analyzed that the quasi-alphabetic writing system of the Aramaic direction entered this region during the Achaemenid period and developed in the form of various scripts until the early Middle Ages. Information is provided about the sources from which these inscriptions have survived. The civilizational significance of writing culture is revealed